Aquatic fungi from peat swamp palms: Phruensis brunneispora gen. et sp. nov. and its hyphomycete anamorph - Pinruan U. (2014)
Phruensis brunneispora is a new genus and species occurring on decaying trunks of the palm Licuala longecalycata in Sirindhorn Peat Swamp Forest, Thailand. We compare the genus with other aquatic ascomycetes with falcate septate ascospores: Pseudohalonectria and Ophioceras. Ascospores differ from species in these genera in being brown with lighter end cells. Also, the ascus pore is subapical, with a channel leading to the apex. Lollipopaia minuta differs from Phruensis brunneispora in that the ascomata are borne in a stroma, asci have an apical pore and the ascospores are hyaline. No genus was found to accommodate the new species. Molecular analysis of rDNA ribosomal 18S confirmed the exclusion of the new species from Pseudohalonectria, and Ophioceras and Lollipopaia minuta formed a sister group with it. Phruensis brunneispora and Lollipopaia minuta grouped in the Diaporthales with 100% bootstrap support. Therefore, both morphological and molecular evidence supports erecting a new genus to accommodate this taxon. A hyaline Phialophora-like anamorph was formed when single ascospores were plated out on agar. The taxon is described and illustrated with light micrographs.